2009
DOI: 10.1158/1541-7786.mcr-08-0309
|View full text |Cite
|
Sign up to set email alerts
|

10-Formyltetrahydrofolate Dehydrogenase–Induced c-Jun-NH2-Kinase Pathways Diverge at the c-Jun-NH2-Kinase Substrate Level in Cells with Different p53 Status

Abstract: 10-Formyltetrahydrofolate dehydrogenase (FDH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…High YAP activity enables the cell to circumvent contact inhibition, induces epithelial-mesenchymal transition, and eventually tumor development [40]. ALDH1L1, on the other hand, is silent in malignant tumors, and its re-expression in cancer cells elicits antiproliferative effects [35,41]. This may explain our finding that ALDH1L1 was highly expressed in astrocytes following YAP knockdown, and that BM-MSC-induced astrocyte proliferation was attenuated due to the subsequent blockage of YAP-TEAD interactions.…”
Section: Discussionmentioning
confidence: 89%
“…High YAP activity enables the cell to circumvent contact inhibition, induces epithelial-mesenchymal transition, and eventually tumor development [40]. ALDH1L1, on the other hand, is silent in malignant tumors, and its re-expression in cancer cells elicits antiproliferative effects [35,41]. This may explain our finding that ALDH1L1 was highly expressed in astrocytes following YAP knockdown, and that BM-MSC-induced astrocyte proliferation was attenuated due to the subsequent blockage of YAP-TEAD interactions.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to its strong down-regulation in cancers (with complete silencing in many cases), 5,11,32 FDH induces distinct apoptotic cascades with c-Jun N-terminal kinases and p53 as downstream mediators. [33][34][35] Canonical tumor suppressor genes, however, have been viewed as those deleted or mutated in cancer, 36,37 which is not the case for ALDH1L1. Numerous studies have also demonstrated epigenetic alterations of tumor suppressor genes in human cancers, which often result in repression of the transcription.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that antiproliferative effects of FDH are associated with activation of JNKs and p53 as downstream effectors ( Ghose et al , 2009 ; Oleinik et al , 2007 ; Oleinik et al , 2005 ). These central players in controlling cellular proliferation are also implicated in regulation of migration ( Roger et al , 2006 ; Williams et al , 2006 ; Xia and Karin, 2004 ).…”
Section: Discussionmentioning
confidence: 99%